Frutas: Practicas de Cuidado de Manejo para los Consumidores - Amy Simonne (EDIS)
FCS8742-Span, a 2-page fact sheet by Amy Simonne, is the Spanish version of Pome and Stone Fruits: Safe Handling Practices for Consumers (FCS8742). It gives guidelines and details on how to safely shop for and prepare pome and stone fruits, such as peaches and apples. Published by the UF Department of Family, Youth, and Community Sciences, June 2007.